Stepping Up to Leadership (LEARNing Landscapes, 2008)
The author shares how her role as leader of Black History Club and the United Cultures Club in her secondary school has helped to shape her understanding of leadership. Through the lenses of "stepping up" and "pushing back," she shows how she has come to a deeper understanding of the role of vision, perseverance, resilience, and delegation in leadership initiatives and, further, how these experiences have benefited her in ways that extend beyond leadership of school clubs.
Keywords: secondary school; leadership; stepping up; vision; perseverance; resilience; delegation